Raíces pragmáticas de la filosofía analítica - Nubiola, Jaime (Sapientia, 2011)
In this paper an overview of the history of analytic philosophy along the Twentieth century is presented, paying special attention to the towering figure of W. V. Quine and highlighting some of the pragmatist roots that probably explain the successful transplant of the logical empiricism of the Vienna Circle to the United States during the second half of the century. The thesis defended is that the analytic tradition in the last decade of the twentieth century and the first decades of the twenty-first is gaining new vigor thanks to the work of Putnam, Rorty, Cavell, MacIntyre, Taylor and others. With the best of the pragmatist tradition, these philosophers are renovating philosophical reflection dealing with the problems of men and women, thus shortening the huge gap between philosophy as an academic discipline and the deepest aspirations of human beings.